(untitled) (ASEAN Engineering Journal, 2024)
The primary objective of this study is to enhance the freshwater production efficiency of a basic seawater distillation apparatus by modifying the condenser pipe. Seawater, initially possessing a salt level of 20%, has undergone treatment via a distillation procedure facilitated by a distillation dispenser. The empirical findings indicated that the utilization of both single and double condenser pipes yielded notable disparities in the generation of freshwater. The initial quantity of freshwater generated by the single condenser pipe was comparatively lower during the course of the trial, whereas the double condenser pipe yielded a greater volume of freshwater over an extended duration. Hence, the careful choice of condenser pipes has the potential to significantly impact the effectiveness and operational capabilities of the distillation dispenser system. The findings of this research offer significant contributions towards the advancement of distillation dispenser technologies that are more efficient, particularly in coastal regions reliant on seawater as a primary water resource. This study has the potential to enhance the accessibility of potable water in regions where obtaining freshwater from natural sources is challenging.